BaP6N10NH:Eu2+ as a Case Study–An Imidonitridophosphate Showing Luminescence. Issue 22 (26th March 2020) - Wendl, Sebastian; Eisenburger, Lucien; Zipkat, Mirjam; Günther, Daniel; Wright, Jonathan P.; Schmidt, Peter J.; Oeckler, Oliver; Schnick, Wolfgang
Abstract: Barium imidonitridophosphate BaP6 N10 NH was synthesized at 5 GPa and 1000 °C with a high‐pressure high‐temperature approach using the multianvil technique. Ba(N3 )2, P3 N5 and NH4 Cl were used as starting materials, applying a combination of azide and mineralizer routes. The structure elucidation of BaP6 N10 NH ( P 63, a= 7.5633(11), c= 8.512(2) Å, Z= 2) was performed by a combination of transmission electron microscopy and single‐crystal diffraction with microfocused synchrotron radiation. Phase purity was verified by Rietveld refinement. 1 H and 31 P solid‐state NMR and FTIR spectroscopy are consistent with the structure model. The chemical composition was confirmed by energy‐dispersive X‐ray spectroscopy and CHNS analyses. Eu 2+ ‐doped samples of BaP6 N10 NH show blue emission upon excitation with UV to blue light ( λ em =460 nm, fwhm=2423 cm −1 ) representing unprecedented Eu 2+ ‐luminescence of an imidonitride. Abstract : The imidonitridophosphate BaP6 N10 NH was synthesized via high‐pressure high‐temperature approach at 4 GPa and 1150 °C. The crystal structure was determined from single‐crystal diffraction data collected with microfocused synchrotron radiation. Doping of the title compound with Eu 2+ leads to unprecedented observation of luminescence from a Eu 2+ ‐doped imidonitridophosphate.